PENGEMBANGAN PERANGKAT PEMBELAJARAN MODEL PROJECT BASED LEARNING (PJBL) MATERI EKOSISTEM UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF PADA SISWA SMA NEGERI 4 AMBON - Makatita, Audrey Louise (Dharmas Education Journal (DE_Journal), 2024)
The selection of appropriate strategies and learning models in the implementation of learning activities can enhance the effectiveness of the students' learning process. This research aims to evaluate the development of instructional tools that integrate the Project-Based Learning (PjBL) model on the topic of ecosystems. The research method used is quantitative descriptive. The evaluation of the results of the development of instructional tools refers to the 4D model, which includes the Define (definition), Design (design), Develop (development), and Disseminate (dissemination) stages. The research findings indicate that the developed instructional tools significantly improve students' understanding of the material and their ability to answer questions, as evidenced by the average student scores falling within the range of 81-85 with a relative frequency of 20%.